Characteristics of High Versus Low-Performing Hospitals for Very Preterm Infant Morbidity and Mortality - Shoshanna Sofaer, DrPH; Kimberly B. Glazer, PhD, MPH; Amy Balbierz, MPH; Anna Kheyfets, BA; Jennifer Zeitlin, ScD; Elizabeth A. Howell, MD, MPP (Elsevier, 2023)
Objective: To ascertain organizational attributes, policies, and practices that differentiate hospitals with high versus low risk-adjusted rates of very preterm neonatal morbidity and mortality (NMM). Methods: Using a positive deviance research framework, we conducted qualitative interviews of hospital leadership and frontline clinicians from September-October 2018 in 4 high-performing and 4 low-performing hospitals in New York City, based on NMM measured in previous research. Key interview topics included NICU physician and nurse staffing, professional development, standardization of care, quality measurement and improvement, and efforts to measure and report on racial/ethnic disparities in care and outcomes for very preterm infants. Interviews were audiotaped, professionally transcribed, and coded using NVivo software. In qualitative content analysis, researchers blinded to hospital performance identified emergent themes, highlighted illustrative quotes, and drew qualitative comparisons between hospital clusters. Results: The following features distinguished high-performing facilities: 1) stronger commitment from hospital leadership to diversity, quality, and equity; 2) better access to specialist physicians and experienced nursing staff; 3) inclusion of nurses in developing clinical policies and protocols, and 4) acknowledgement of the influence of racism and bias in healthcare on racial-ethnic disparities. In both clusters, areas for improvement included comprehensive family engagement strategies, care standardization, and reporting of quality data by patient sociodemographic characteristics. Conclusions and relevance: Our findings suggest specific organizational and cultural characteristics, from hospital leadership and clinician perspectives, that may yield better patient outcomes, and demonstrate the utility of a positive deviance framework to center equity in quality initiatives for high-risk infant care.